The Muslim Woman's Personality and the Development of Insan Kamil in the Novels of Faisal Tehrani and Isa Kamari (Malay Literature, 2013)
This study will show the characteristics of the Muslim woman who is capable of becoming a good example (uswah hasanah) for readers. Apart from this, the researcher wishes to show the extent to which the authors are able to handle Muslim women characters that are able to build and encourage readers towards becoming insan Kamil. In this matter the characteristics of the Muslim woman in Faisal Tehrani's Tunggu Teduh Dulu (Wait Till It Cools) and Surat-surat Perempuan Johor (The Letters of the Johor Woman), as well as Isa Kamari's novels Atas Nama Cinta (In the Name of Love) and Satu Bumi (One Earth) will be examined. The characteristics of the Muslim woman that play a role in the development of insan Kamil will be examined in light of the Takmilah Theory which focuses on the principle of developing an audience of insan Kamil. The depiction of women whose personalities display the characteristics of insan Kamil is hoped to be able to exemplify the human ideal for readers.Keywords: Muslim womens personality; Takmilah Theory; Insan Kamil, Faisal Tehrani, Isa Kamari